Lessons in teaching grammar in primary schools - Horton, Suzanne; Bingle, Branwen (Los Angeles, CA : SAGE Publications, Inc., 2014)
Lecturer copy Trainee teachers often seek examples of effective teaching of grammar in primary schools. As many teachers themselves express a lack of confidence in their own knowledge of grammar, where do trainees find exemplar lessons? This book provides them. It takes exemplar lessons and offers them alongside a detailed exploration of what makes them good, and the theory behind them. The text encourages trainees to consider the teaching of grammar critically and to envisage how they can shape lessons for their own teaching. In starting with teaching then exploring theory, the text mirrors how many trainees will learn.
Includes bibliographical references and index.
Description based on XML content.
Keywords: English language -- Grammar -- Study and teaching (Primary) -- Great Britain; English language -- Composition and exercises -- Study and teaching (Primary) -- Great Britain